Analisis Mediasi Kinerja Keuangan dalam Pengaruh Green Accounting terhadap Nilai Perusahaan - Ahmad, Nice Agustin; Aspuri, Muhamad; Adawiyah, Syaripatul; Putri, Dhea; Letsoin, Supyati (CV. ITTC INDONESIA, 2025)
Climate change issues and sustainability regulations have encouraged companies to implement green accounting. However, the effectiveness of its implementation in enhancing firm value remains debated, particularly in the consumer non-cyclicals sector, which is highly exposed to environmental and social pressures. This study aims to analyze the effect of green accounting on firm value, with financial performance as a mediating variable. The research was conducted on consumer non-cyclicals companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. Green accounting was measured using the disclosure coverage level based on the GRI 300 series, financial performance was proxied by Return on Assets (ROA), and firm value was measured using the Tobin’s Q ratio. This study employed a quantitative associative approach with an explanatory research design. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS software. The results show that green accounting does not significantly affect firm value or financial performance. Furthermore, financial performance does not have a significant effect on firm value and does not mediate the relationship between green accounting and firm value. The practical implication of these findings suggests that companies need to enhance the substantive quality of green accounting practices to positively impact profitability and investor perception. Academically, this study offers opportunities for future research by incorporating control variables such as firm size, leverage, or ESG scores to strengthen the model.